Ajokertutsit [electronic resource] : pijarialiksuit tellimat. - Erdmann, Friedrich, 1810-1873.; Moravian Church. (Herrnhuteme [Herrnhut, Germany] : G. Winterib nênilauktangit, 1906)
Translated by Friedrich Erdmann--Pilling. "Pp. 25-26 contain the multiplication table"--Pilling. "Katechismus. Unveränderter Abdruck der Auflage von 1883." "Catechism in the Eskimo language of Labrador"--Pilling. Pilling (Eskimo), Banks (2nd ed.), Electronic reproduction. Mode of access: Internet. 44